A Fine Balance - Sye, Jill (Auckland University of Technology, 2008)
The aim of this study is to analyse the discourses drawn upon by community paediatric nurses in relation to children’s rights to health. The philosophy of Michel Foucault has been used to underpin the analysis of the interviews and exemplars of five experienced community nurses, revealing conflicting power relationships and discourses. Rights are formalised morality and so from a children’s rights perspective, discourses reflect both the moral and ethical positions of the nurses. Children are constructed as developing human beings whose moral status gradually changes and who, through a lack of developmental autonomy, entrust their decision-making to their representatives (parents and caregivers) as their trustees. Rights are correlative with the obligations and duties toward children by both families and society. Society constructs legislative and politically organised structures to govern raising children because children are an intrinsic social concern. Whilst representing society’s interest in children’s rights to health, nurses in the home act as a conduit for multiple governing structures. The nurses in this study construct their “truths” and knowledge about children’s health rights from nursing, medicine, law, education, and social policy. However, the values of individual parents can conflict with universal values for children’s health and wellbeing. Therefore representing society positions nurses as “agents of the state”, a role that potentially holds power over parents and children and leads to the epithet of “the health police”. Within the institution of the family, and in the privacy of the home, there are also mechanisms of power that can resist the mechanisms of the state and its representatives. Therefore the discourse “it takes a village to raise a child” competes with the “my home is my castle” discourse. Nurses negotiate a fine balance between these power relations. Nurses are challenged with using power productively to promote children’s rights whilst respecting the role of parents and families. I argue that children’s rights are central to the moral and ethical work of nurses but that such work is often obscured and invisible. I propose that children’s community nurses are excellent at negotiating networking and connecting at a micro level, but need to create a more sophisticated and cohesive entity at a macro level to become fully political children’s rights advocates.
Keywords: Discourse analysis; Community children's nurses perceptions and practices; Childrens rights to health; Family centred care discourse; Child centred discourse